Transformasi Penyampaian Pesan Harian Rakyat Maluku Dalam Mendapatkan Iklan dan Advetorial - Yusmanizar, Yusmanizar; Azzuhry Rumra, Syaikhan (Palita: Journal of Social Religion Research, 2024)
This study was aimed to determine and analyze the transformation of daily message delivery of the people of Maluku in getting advertisements and advertorials. The method used is qualitative research with a case study research method. The data collection used in-depth interview, observation, and document study. Data analysis used discourse analysis by observing and analyzing how messages are structured in the daily print media Rakyat Maluku. The results showed that 3 transformations of delivery were conducted by the daily Rakyat Maluku in obtaining advertisements and advertorials, namely Template Ads (Banner Ads), Insert Ads, Advertorial through social media. The transformation of messages conducted did not even switch off print media as the main business choir. Digital and print media were successfully integrated to achieve the company's target.